Mother’s health care-seeking behavior for children with acute respiratory infections in a post-earthquake setting - Yulinar Wusanani; Djauhar Ismail; Rina Triasih (Indonesian Pediatric Society, 2013)
Background Delayed health care-seeking behavior is a causeof high mortality in children due to acute respiratory infections(ARis). Factors that may affect health care-seeking behavior aresocioeconomic status, maternal age, maternal education, parents'perception of illness, child's age, number of children under fiveyears of age in the family, and occurrence of natural disasters. The2006 Central Java earthquake damaged homes and health carefacilities, and led to increased poverty among the residents.Objective To assess the relationship between socioeconomicstatus and mother's health care-seeking behavior for childrenunder five years of age with ARis in a post-earthquake setting.Methods This cross-sectional study used secondary data obtainedfrom the Child Health Need Assessment (CHNA) survey. Logisticregression test was used to analyze variables that may affectmother's health care-seeking behavior for children under fiveyears of age with ARis.Results Of the 665 infants surveyed, 442 infants (66.5%)had ARis. Health care-seeking behavior was good (81.7%)in the majority of mothers. We observed that socioeconomicstatus did not affect maternal health care-seeking behavior forchildren under five with ARis (OR 1.33; 95%CI 0.79 to 2.24;P= 0.26). Maternal age, maternal education, child's age andgender, number of children under five in the family, parents'perceptions of illness and severity of house damage caused by theearthquake also had no effect on maternal health care-seekingbehavior for children with ARis.Conclusion After the 2006 earthquake, we find that socioeconomicstatus, maternal age, maternal education, child age, child gender,number of children under five in the family, parents' perceptionsof illness, and severity of house damage have no effect on mother'shealth care-seeking behavior for their children with ARis.